2003
DOI: 10.1046/j.1460-9592.2003.t01-1-00173.x
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Thrombus Formation Without Impedance Rise During Radiofrequency Ablation Using Electrode Temperature Control

Abstract: The authors hypothesized that during RF ablation, the electrode to tissue interface temperature may significantly exceed electrode temperature in the presence of cooling blood flow and produce thrombus. In 12 anesthetized dogs, the skin over the thigh muscle was incised and raised to form a cradle that was superfused with heparinized canine blood (ACT > 350 s) at 37 degrees C. A 7 Fr, 4-mm or 8-mm ablation electrode containing a thermocouple was held perpendicular to the thigh muscle at 10-g contact weight. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 23 publications
(28 reference statements)
3
81
0
1
Order By: Relevance
“…In the case of constant temperature, Matsudaira et al [37] found experimentally that temperature distribution in the blood was clearly non symmetrical around the electrode axis, with higher values on the side opposite the blood flow. They also found that the maximal temperature in the blood was 68.3±4.3ºC with a 4-mm electrode after 60 seconds of ablation, 55ºC target temperature, and high blood flow condition.…”
Section: B Comparison With Experimental Resultsmentioning
confidence: 99%
“…In the case of constant temperature, Matsudaira et al [37] found experimentally that temperature distribution in the blood was clearly non symmetrical around the electrode axis, with higher values on the side opposite the blood flow. They also found that the maximal temperature in the blood was 68.3±4.3ºC with a 4-mm electrode after 60 seconds of ablation, 55ºC target temperature, and high blood flow condition.…”
Section: B Comparison With Experimental Resultsmentioning
confidence: 99%
“…As demonstrated previously, in high-blood-flow states, there is an increased tissue-tocatheter-tip temperature discrepancy in a tissue-bath model in comparison with low-blood-flow states. 9 In the canine model, a perpendicular tip/tissue orientation in the right superior PV is difficult to achieve because of the angle created in the small left atrium. Furthermore, a parallel position is difficult to achieve in the right superior PV without entering the PV.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the temperature recorded at the catheter tip accurately reflects tissue temperature at times or if an extensive "cooled-tip" effect is present near the PV orifice. 9 Therefore, the purposes of this study were to (1) determine the catheter-tip versus tissue temperature profile during ablation with an 8-mm tipped catheter, (2) determine the clinical factors that may result in inaccurate catheter-tip reflection of actual tissue temperatures, and (3) evaluate the impact of repetitive burns at a single site on the dynamics of tissue heating.…”
mentioning
confidence: 99%
“…However, the high incidence of thrombus formation without impedance rise during RF ablation using electrode temperature control (69% with a catheter-tip temperature of 65°C) using 4-mm tip conventional ablation catheter was reported previously. 15 Thus, an irrigation catheter might be safer conventional ablation catheter when higher power ablation is expected.…”
Section: Study Limitationsmentioning
confidence: 99%